Electrocardiographic predictors of atrial fibrillation in patients with cryptogenic stroke. Issue 2 (13th January 2022) - de Leon, Ana; Neira, Victor; Alhammad, Nasser; Hopman, Wilma; Hansom, Simon; Chacko, Sanoj; Simpson, Chris; Redfearn, Damian; Abdollah, Hoshiar; Arauz, Antonio; Baranchuk, Adrian; Enriquez, Andres
Abstract: Background: Empiric anticoagulation is not routinely indicated in patients with cryptogenic stroke without documentation of atrial fibrillation (AF). Therefore, identification of patients at increased risk of AF from this vulnerable group is vital. Objectives: To identify electrocardiographic (ECG) predictors of AF in patients with cryptogenic stroke or transient ischemic attack (TIA) undergoing insertion of an implantable cardiac monitor (ICM). Methods: In this single‐center study, 48 patients with cryptogenic stroke or TIA had an ICM implanted for detection of AF between January 2013 and September 2019. Patients with and without AF were compared in terms of p‐wave duration and a novel index (MVP score). Results: During a mean follow‐up of 16 ± 14 months, AF was detected in seven patients (15%). Diagnosis of AF was made after a mean of 10 ± 14 months, with time to first AF detection ranging between 1 and 40 months. Patients with AF had a longer p‐wave duration (136 ± 9 ms vs. 116 ± 10 ms; p = .0001) and a higher MVP score (4.5 ± 1.2 vs. 2.0 ± 0.9, p = .0001) than those without AF. Advanced interatrial block (IAB) was observed in 43% of patients with ICM evidence of AF and 0% of those without AF ( p = .002). Age, LA size or LVEF were not predictors of AF. Conclusion: An increased p‐wave duration, advanced IAB and high MVP score are associated with AF occurrence in patients with cryptogenic stroke. Identifying patients with these markers may be helpful as they may benefit from more exhaustive and prolonged monitoring.